Extracellular production of avicelase by the thermophilic soil bacterium Bacillus sp. SMIA-2 - Luciana Ribeiro Coutinho Oliveira (Acta Scientiarum. Biological Sciences, 2014)
Nowadays, the isolation of new bacterial strain s that produce enzymes with novel properties is a subject of great relevance to the scientific communi ty. This study, in order to search for producers of new cellulase strains, investigated the avicelase production by thermophilic Bacillus sp. strain SMIA-2. The best avicelase activity was observed in a culture medium containing 0.5% (w v -1 ) avicel and 0.5% (w v -1 ) corn steep liquor with initial pH 7.5-8.0 incubated at 50 o C. When avicel was replaced in the medium by the treated sugarcane bagasse (0.5%, w v -1 ) the avicelase activity levels were not affected. Studies on the avicelase characterization revealed that the optimu m pH of the enzyme was found to be 8.5 and the enzyme retained more than 80% of its activity after in cubation at room temperatur e for 2h at pH 6.5-8.5. The optimum temperature of this enzyme was 70 o C and the enzyme retained 67% of the original activity after 20 min. of heat treatment at 70 o C. Avicelase was stimulated by Mn 2+ and Co 2+ , whereas Hg 2+ greatly inhibited the enzyme activity.